Mature and emerging organic markets: Modelling consumer attitude and behaviour with Partial Least Square Approach - Marie von Meyer-Höfer; Vera von der Wense; Carlos Padilla Bravo; Achim Spiller (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2013)
Although the organic food sector has been the subject of research for around 20 years, little is known about consumer behaviour when comparing developed and emerging organic food markets using causal research models. Thus, by developing a behavioural model based on the Theory of Planned Behaviour (TPB), the aim of this research article is to investigate the main determinants of organic food consumption in a mature (Germany) and an emerging (Chile) organic market. Subjects aged 18 or above were consulted about their attitudes towards, intention to consume, and stated consumption behaviour of organic food via an online survey in both countries. Items related to social norms and perceived behaviour control (PBC) were also included in the assessments. Exploratory factor analysis was used to identify key constructs in the proposed research model. Afterwards, a partial least squares (PLS) approach was used to assess causal relationships, and significant differences between countries were also tested. The proposed behavioural model was suitable for predicting individuals' behaviour in Chile and Germany. Nevertheless, the findings indicate that the model was able to explain more variance in Germany than in Chile. In line with the TPB, intention to buy organic food is a good predictor of behaviour. In addition, both altruistic and egoistic arguments are significant drivers of attitude towards and intention to buy organic food in Germany. In Chile, only altruistic motives have a significant impact on consumer attitude and intentions. The results of this study have implications for marketers and policy-makers in both countries. The use of altruistic arguments in organic food marketing is a key aspect that should be considered in communication campaigns to increase organic food demand in both countries. However, along with the evolution of the organic market in Chile, egoistic aspects related to organic consumption might also gain importance in determining consumer behaviour, as is already the case in Germany. In both countries, information should be comprehensive and communicated by a credible source to enable growing consumer trust in the organic food sector as a sustainable alternative to conventional food supply. The barriers that deter organic food consumption have to be addressed by marketers and policy-makers with great attention; these include not only information but also the lack of availability, especially in Chile, and scepticism about organic food in Germany.
Keywords: Q13; Q18; 330; Organic food; Consumer behaviour; Partial least squares; Germany; Chile